Quantification of Zonula Occludens-1 mRNA expression in cultured bovine retinal endothelial cells, using SYBR green real-time PCR - Muniandy, S.; Yaiw, K.C.; Chook, J.B.; Rayappan, A.V.; Wong, K.T.; Ismail, I.S.; Qvist, R. (2008)
A simple and rapid real-time reverse transcription-PCR (RT-PCR) technique using SYBR green fluorescence was developed to quantify Zonula Occludens-1 (ZO-1) mRNA expression in histamine-treated cultured bovine retinal microvessel endothelial cells. There was no difference between the quantity of ZO-1 mRNA expression in histamine-treated (10(-7)M to 10(-9) M) and untreated bovine retinal endothelial cells at high magnesium levels. Immunohistochemistry staining and western blot assay unequivocally demonstrated the approximately similar levels of ZO-1 protein in both histamine-treated and non-treated endothelial cells at high magnesium concentrations.